ANALISIS FAKTOR-FAKTOR DETERMINAN KEENGGANAN MUZAKKI MEMBAYAR ZAKAT KE BADAN AMIL ZAKAT (Studi Kasus Baznas Kabupaten Padang Lawas Utara) - Juliana Sari Harahap; Andri Soemitra; Zuhrinal M. Nawawi (ITB AAS INDONESIA Surakarta, 2022)
In general, the majority of the people of North Padang Lawas Regency (PALUTA) are Muslims with a population of approximately 269,845 people. However, according to a survey conducted, researchers found a fact that the majority of people in North Padang Lawas Regency did not even pay zakat to BAZNAS and gave zakat directly to mustahiq, not to institutions to be managed. In 2019 there was only 1 muzakki, in 2020 there were none at all and for 2021 again there was only 1 muzakki. And the survey conducted, the researchers found that the driving factors for the people of North Padang Lawas Regency were reluctant to pay zakat to the Baznas office including location factors, lack of socialization, lack of trust, and lack of knowledge. The purpose of this study was to determine the effect of location variables, lack of socialization, lack of trust, and literacy on muzakki's reluctance to pay zakat to the National Amil Zakat Agency of North Padang Lawas Regency. This research method uses a quantitative approach and uses SPSS version 20.0 program assistance. This study used a questionnaire with a sample of 100 respondents. The results showed partially that location had an effect, lack of socialization partially had an effect, lack of trust partially had an effect and literacy partially affected the reluctance of muzakki to pay zakat to the National Amil Zakat Agency, North Padang Lawas Regency. From the results of the significance test, it was found that location, lack of socialization, lack of trust, and literacy had a significant and significant effect on muzakki's reluctance to pay zakat to the National Amil Zakat Agency of North Padang Lawas Regency. Keywords: Location, lack of socialization, lack of trust, literacy, and reluctance.